Analisis Beban Kerja dan Kebutuhan Sumber Daya Manusia dengan Metode WISN pada Rumah Sakit Umum Tipe C di Medan - Daniel Ginting; Nina Fentiana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The availability of human resources (HR) in hospitals is a key factor in ensuring quality healthcare services. A type C general hospital in Medan faces challenges in terms of limited health personnel in several service units. The Workload Indicators of Staffing Need (WISN) method by WHO is applied to calculate staffing requirements based on actual workload. This study aimed to analyze the workload and HR needs of a type C general hospital in Medan using the WISN method. A quantitative descriptive study with a WISN approach. Data were obtained from hospital management reports including patient visits, bed occupancy rate (BOR), and staff distribution across main units. Analysis was carried out by calculating available working time, workload standards, allowance standards, and HR needs per unit. The analysis indicated shortages of personnel in several units: inpatient nurses (−20), anesthetists (−2), pharmacists (−1), laboratory analysts (−5), radiographers (−5), and medical records staff (−6). Some units had surplus staff, such as maternity (+8). The type C general hospital in Medan continues to face HR shortages in critical service units. Workload-based HR planning using the WISN method is crucial to support effective recruitment and staff redistribution.